Analysis of Waiting Time for Patient Service Using Lean Concept in Outstanding Installations Stella Maris Hospital - Muhammad Takwa; Andi Niartiningsih; Nurul Hidayah Nur; Nurfitriani Nurfitriani; Mene Paradilla (International Journal of Medicine and Health, 2025)
Hospitals worldwide are increasingly concerned about the performance of outpatient services, which contribute significantly to their revenue and are projected to surpass inpatient services in importance. As the demand for medical care continues to grow, outpatient services could generate even greater financial returns for hospitals. This study aims to evaluate patient service wait times at Stella Maris Hospital Makassar's outpatient department using the lean methodology. A mixed-methods approach was employed, involving the measurement of wait times for 100 patients and interviews with eight informants, including the head of the outpatient department (1 person), admission officers (3 individuals), the hospital director (1 person), and nurses (3 individuals). The interview data were analyzed through processes of data reduction, visualization, and conclusion formulation. A patient care process flowchart was created to assess data quality. Findings indicate the absence of an integrated hospital information system (SIMRS), leading to issues such as long queues at the pick-up counter, delays in doctor availability, and inefficiencies in order processing. Recommendations include integrating SIMRS across the hospital, implementing system improvements, and quantifying outcomes for effective decision-making.